2015
DOI: 10.1016/j.addbeh.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Reward sensitivity, attentional bias, and executive control in early adolescent alcohol use

Abstract: This study examined whether attentional bias for alcohol stimuli was associated with alcohol use in young adolescents, and whether the frequently demonstrated relationship between reward sensitivity and adolescent alcohol use would be partly mediated by attentional bias for alcohol cues. In addition, this study investigated the potential moderating role of executive control (EC), and tested whether the relationship between alcohol-related attentional bias and alcohol use was especially present in young adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 54 publications
5
39
1
Order By: Relevance
“…Although not all of our findings conformed to our predictions, the current study adds to the small body of work demonstrating the moderating role of cognitive capacities on the impact of alcohol-related cognitions on adolescent alcohol use (Peeters et al, 2013; van Hemel-Ruiter et al, 2015). Additionally, the current study highlights the complexity of descriptive and injunctive norms and points to the need for future work to identify unique moderating mechanisms of these normative influences.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Although not all of our findings conformed to our predictions, the current study adds to the small body of work demonstrating the moderating role of cognitive capacities on the impact of alcohol-related cognitions on adolescent alcohol use (Peeters et al, 2013; van Hemel-Ruiter et al, 2015). Additionally, the current study highlights the complexity of descriptive and injunctive norms and points to the need for future work to identify unique moderating mechanisms of these normative influences.…”
Section: Discussionsupporting
confidence: 49%
“…Several dual-process models of addictive behaviors posit that whether alcohol-related cognitions, such as alcohol expectancies and implicit alcohol associations, influence decisions to drink depends on executive functions related to self-regulation. Several studies have supported this moderating role of executive self-regulation (Jonker, Ostafin, Glashouwer, van Hemel-Ruiter, & de Jong, 2014; Peeters et al, 2013; van Hemel-Ruiter, de Jong, Ostafin, & Wiers, 2015). Similar to work on dual-process models, social norms researchers have forwarded the idea that two cognitive factors closely tied to executive functions, cognitive reflection and inhibitory control (IC), may influence whether a descriptive or injunctive norm will guide behavior (Jacobson et al, 2011; Kredentser et al, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…Other research has shown, however, that this effect may only emerge when stimuli are presented for longer durations (i.e. 500-2000 ms vs. 200 ms; Field et al 2004), and for those with lower effortful control (van Hemel-Ruiter et al 2015). Recently, the visual probe task has been shown to suffer from low internal and test-retest reliability (Jones et al 2018; see also Ataya et al 2012;Field and Christiansen 2012), which may explain the heterogeneity of previous findings.…”
Section: Introductionmentioning
confidence: 94%
“…Specific groups may respond differently to alcohol consumption and may have more difficulty in adapting their drinking pattern whenever needed. In general, it has been extensively described that adolescents are less sensitive to the negative effects of alcohol, including cues that influence self-regulation of intake, but are more sensitive to positive effects, which may serve to reinforce or promote excessive intake [41]. This response to alcohol may promote the development of alcohol use disorders, a development university students may be less vulnerable to as compared to other groups of adolescents [7].…”
Section: Discussionmentioning
confidence: 99%